POTENSI KEARIFAN LOKAL TANAMAN Ficus SEBAGAI ANTIOKSIDAN - Syamsuri Syakri; Mukhriani Mukhriani; Kairun Nisa; St. Aisyah S (Universitas Islam Negeri Alauddin Makassar, 2021)
The Ficus plant is made up of roughly hundreds of species that are scattered across South, Southeast Asia, and there are 76 types of Ficus plants in Indonesia. Ficus is a plant that is widely used for the prevention of various diseases. Several recent studies have shown that the Ficus plant also has antioxidant activity. This work has described the antioxidant potential of the Ficus plant. Overall, these data suggest that Ficus wood can be suggested as as cosmetic ingredient. The bibliographic survey was conducted from January 2016 to April 2020 by analyzing peer-reviewed journals and articles from the past five years. Peer-reviewed articles were indexed by PubMed, GoogleScholar, DOAJ, and ScienceDirect. Only relevant studies published in English and Indonesian will be considered. There are 31 articles reporting the antioxidant activity of Ficus in vitro on DPPH, FRAP and ABTS methods. Based on a review of these articles, we conclude that ficus has the potential to be developed as an antioxidant cosmetic.